Deepwater Horizon 2010: Subsea dispersants protected responders from VOC exposure. (December 2021) - Zhao, Lin; Mitchell, Douglas A.; Prince, Roger C.; Walker, Ann Hayward; Arey, J. Samuel; Nedwed, Tim J.
Abstract: Controversy remains on the use of Sub-Sea Dispersant Injection (SSDI) during the Deepwater Horizon (DWH) spill to minimize the exposure of responders on surface vessels to volatile organic compounds (VOC). Here, we use extensive evidence (>90, 000 VOC measurements) collected near the oil well MC252 site during the DWH spill and demonstrate at a high level of statistical confidence that SSDI enhanced the safety and health conditions of the responders at the water surface through the reduction of airborne VOC concentrations in a dose-dependent manner. VOC levels on ships' decks were clearly diminished ( p < 0.001) during subsea dispersant use, and incidents of peak concentrations (>50 ppm VOC) that could have been an immediate concern to worker health were reduced by a factor of 6 to 19 when dispersants were delivered at the intended rate. SSDI thus played an important role in minimizing potential exposure to VOC, and should be embedded in guidelines and regulations for dispersant use. Highlights: Thousands of VOC data collected near Deepwater Horizon spill site are analyzed Statistical evidence indicates that SSDI did indeed reduce worker exposure to VOC Incidents of peak concentrations were reduced by 6 to 19 fold by SSDI Data suggest that a more prompt use of dispersant would further reduce VOC exposure